Esterification Bio-oil using Acid Catalyst and Ethanol - Rian C Sondakh; Erliza Hambali; Nastiti S Indrasti (International Journal of Engineering and Management Research, 2018)
Fuel energy sources are limited. It is necessary to obtain alternative energy that can be reached. Bio-oil is one of the promising renewable energy that production of bio-oil derived from agricultural wastes and industrial wastes by fast pyrolysis process but the quality bio-oil is not good as bio-fuel it needs upgrading method. One of the methods to upgrading bio-oil is using esterification. Esterfication method reduces viscosity, density, and ash. The purpose of this research was to increasing bio-oil quality by type of acid catalyst. Catalyst used was H2SO4, HCl and citric acid, concentration catalyst was used according to free fatty acid (FFA) and free fatty acid was 5.09 before esterification. The bio-oil after esterification show FFA lower than 2.00 and indicate it worked. Esterification with acid catalyst shows some critical change like acid number, viscosity kinematic, density, pH, and ash. The result found acid number 0.64, 1.02 and 3.39 Mg of KOH/g, viscosity kinematic 11.61, 11.83, and 13.64 cSt @40oC, density 1.11, 1.12 and 1.21 kg/dm3 @20 oC, pH values 2.05, 2.33 and 3.06, ash 0.0003, 0 and 0.004. The concentration catalyst according to FFA with esterification process has a good impact on bio-oil characteristics according to standards and its high activity.